Changing Trends in the Management of Esthesioneuroblastoma: Irish and International Perspectives - Woods, Robbie S. R.; Subramaniam, Thavakumar; Leader, Mary; McConn-Walsh, Rory; O'Neill, James Paul; Lacy, Peter D. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objectives Evaluation of the changing trends in esthesioneuroblastoma in an Irish context and review of management options nationally to clarify the best current therapeutic approach by comparing with international research on this uncommon malignancy.Design Retrospective review.Setting Tertiary referral center.Participants All patients presenting with esthesioneuroblastoma in Beaumont hospital or on the National Cancer Registry of Ireland between 1994 and 2013.Main Outcome Measures Recurrence-free and overall survival.Results During the study period, 32 cases of esthesioneuroblastoma were diagnosed (0.4 per million per year). Average age at diagnosis was 57 years; however, two cases were under 20. The majority (62.5%) were male. Patients predominantly presented with epistaxis or nasal congestion (73%), while two cases were identified incidentally on radiological investigations. Twenty-seven cases underwent primary surgical management (two post neo-adjuvant treatment) with seventeen requiring bifrontal craniotomy. Twenty-four of these received postoperative radiation therapy. Overall, 5-year survival was 65%. Kadish A/B patients exhibited 100% 5-year disease-specific survival versus 54% in Kadish C/D (p = 0.011). Hyams grade I/II patients exhibited 75% 5-year disease-specific survival versus 63% in Hyams grade III/IV (p = 0.005). Patients treated endoscopically exhibited 100% 5-year disease-specific survival versus 51% in those treated via an open approach (p = 0.102).Conclusions Many controversies exist in the diagnosis and management of this condition. Despite this, results from Irish data are mostly concordant with the international literature. The rising incidence of this disease may represent improved pathological recognition. An increasing number of esthesioneuroblastoma cases are being successfully treated via endoscopic surgery.
Keywords: esthesioneuroblastoma; sinonasal malignancy; olfactory neuroblastoma; skull base